Empowering Halal Industry: Strategi Pemanfaatan Investasi Syariah Terhadap Pengembangan Ekosistem Bisnis Halal di Indonesia - Ai Jamilah; Panji Adam Agus Putra; Nandang Ihwanudin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze strategies for utilizing sharia investment in empowering the halal business ecosystem in Indonesia. The method used is a Systematic Literature Review (SLR) with thematic analysis of publications from 2020 to 2025. The results show that Islamic investment through Islamic stocks, sukuk, mutual funds, fintech, and blended finance has great potential to finance and strengthen the halal value chain from corporations to MSMEs. However, its utilization is still hampered by low Islamic financial literacy, limited access for MSMEs, fragmented regulations, and suboptimal supporting infrastructure. Based on the analysis, an empowerment strategy based on the Halal Ecosystem Integration Model (HEIM) was formulated, emphasizing: (1) strengthening sharia financing infrastructure; (2) accelerating halal certification for MSMEs; (3) integrating the halal value chain; and (4) increasing literacy and human resource capacity. In conclusion, Islamic investment can serve as a catalyst for inclusive and sustainable halal industry empowerment, in line with the principles of maqashid syariah, if supported by integrated strategies and synergistic policies from all stakeholders.